Kesenjangan Struktural antara Penegakan Represif dan Rehabilitasi Sosial Berkelanjutan dalam Penanganan Kelompok Perkotaan yang Terpinggirkan di Kabupaten Banyumas - Araska Arkananta Celesta; Tutik Wijayanti (Universitas Tribhuwana Tungga Dewi, 2026)
The increasing number of beggars, vagrants, and homeless people (BVH) in Banyumas Regency highlights the limitations of social welfare policies in addressing these issues sustainably. Previous studies have tended to focus on aspects of enforcement, control, or partial rehabilitation, while policy evaluations that integrate implementation performance and inter-agency governance at the local level remain limited. This study aims to evaluate the effectiveness, adequacy, responsiveness, and equity of BVH management policies for the 2020–2024 period and to analyze governance between the Social Affairs Office and the Civil Service Police Unit (Satpol PP). The study employs a descriptive qualitative method using a case study approach in South Purwokerto Subdistrict, selected due to high community mobility and the intensity of BVH presence. There were five informants, consisting of two functional officials for social rehabilitation from the Social Affairs Office, one section head from the Community Police Unit, one shelter manager, and one community member selected through purposive sampling. Data collection was conducted through in-depth interviews and field observations over a seven-day period. Research data included Banyumas Regency Regulation No. 16 of 2015 as well as BVH statistical data from the publication Banyumas in Figures for the 2020–2024 period. Analysis utilized William N. Dunn’s policy evaluation framework and Edwards III’s (1980) implementation model. Results indicate that implementation remains dominated by a temporary repressive approach, while rehabilitation efforts are limited due to resource constraints and insufficient service capacity. Policy performance is also influenced by weak inter-agency governance, particularly structural fragmentation, communication barriers, and the absence of integrated technical regulations.Meningkatnya jumlah Pengemis, Gelandangan, dan Orang Terlantar (PGOT) di Kabupaten Banyumas menunjukkan keterbatasan kebijakan kesejahteraan sosial dalam menangani permasalahan secara berkelanjutan. Penelitian terdahulu cenderung menitikberatkan aspek penertiban, pengendalian, atau rehabilitasi secara parsial, sementara evaluasi kebijakan yang mengintegrasikan kinerja implementasi dan tata kelola antarinstansi daerah masih terbatas. Penelitian ini bertujuan mengevaluasi efektivitas, kecukupan, responsivitas, dan perataan kebijakan penanganan PGOT periode 2020–2024 serta menganalisis tata kelola antara Dinas Sosial dan Satuan Polisi Pamong Praja. Penelitian menggunakan metode kualitatif deskriptif dengan pendekatan studi kasus di Kecamatan Purwokerto Selatan yang dipilih karena tingginya mobilitas masyarakat dan intensitas PGOT. Informan berjumlah lima orang, terdiri dari dua pejabat fungsional rehabilitasi sosial Dinas Sosial, satu kepala seksi Satpol PP, satu pengelola rumah singgah, dan satu anggota masyarakat yang dipilih purposive. Pengumpulan data melalui wawancara mendalam dan observasi lapangan selama tujuh hari. Data penelitian meliputi Peraturan Daerah Kabupaten Banyumas Nomor 16 Tahun 2015 serta data statistik PGOT dalam publikasi Banyumas dalam Angka periode 2020–2024. Analisis menggunakan kerangka evaluasi kebijakan William N. Dunn dan model implementasi Edwards III (1980). Hasil menunjukkan implementasi masih didominasi pendekatan represif temporer, sedangkan rehabilitasi terbatas akibat keterbatasan sumber daya dan kapasitas layanan. Kinerja kebijakan juga dipengaruhi lemahnya tata kelola antarinstansi, terutama fragmentasi struktural, kendala komunikasi, dan belum tersedianya regulasi teknis terintegrasi.